Constitutive and Stress-Induced Psychomotor Cortical Responses to Compound K Supplementation - Flanagan, Shawn D.; Proessl, Felix; Dunn-Lewis, Courtenay; Canino, Maria C.; Sterczala, Adam J.; Connaboy, Chris; DuPont, William H.; Caldwell, Lydia K.; Kraemer, William J. (Frontiers in Neuroscience, 2020)
Isolated ginsenoside metabolites such as Compound K (CK) are of increasing interest to consumer and clinical populations as safe and non-pharmacological means to enhance psychomotor performance constitutively and in response to physical or cognitive stress. Nevertheless, the influence of CK on behavioral performance and EEG measures of cortical activity in humans is undetermined. In this double-blinded, placebo-controlled, counterbalanced within-group study, dose-dependent responses to CK (placebo, 160mg, 960mg) were assessed after two weeks of supplementation in nineteen healthy men and women (age: 39.9±7.9yr, height 170.2±8.6cm, weight 79.7±11.9kg). Performance on upper- and lower-body choice reaction tests (CRTs) was tested before and after intense lower-body anaerobic exercise. Treatment- and stress-related changes in brain activity were measured with high-density EEG based on event-related potentials, oscillations, and source activity. Upper- (-12.3±3.5ms, p=0.002) and lower-body (-12.3±4.9ms, p=0.021) response times improved after exercise, with no difference between treatments (upper: p=0.354; lower: p=0.926). Analysis of cortical activity in sensor and source space revealed global increases in cortical arousal after exercise. CK increased activity in cortical regions responsible for sustained attention and mitigated exercise-induced increases in arousal. Responses to exercise varied depending on task, but CK appeared to reduce sensory interference from lower-body exercise during an upper-body CRT and improve the general maintenance of task-relevant sensory processes.